(untitled) (Journal of Dhaka Medical College, 2015)
Context: The variation in anatomical features of sacral hiatus and the dorsal wall of sacral canal is related to its clinical application in caudal epidural anesthesia. Through the sacral hiatus, it is employed in operation in the anal region and on the external genital organs, as well as cystoscopic examination of male. Continuous caudal anesthesia is also used in obstetrics during parturition for better cervical dilatation and shortening the first stage of labor. Methods: The present study was performed on 172 (one hundred seventy two) adult human dry sacra of unknown sex. The study samples were distributed in male and female sex groups by discriminant function analysis. The study was cross sectional analytical type and was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from January 2011 to December 2011. The various landmarks of sacral hiatus were measured with the help of digital slide calipers. Results: The mean length of sacral hiatus in male and female was found 26.38±12.02 mm and 25.63±10.46 mm respectively. The mean anterior-posterior diameter of sacral hiatus at the apex was found 4.76±1.73 mm in male and 4.92±2.13 mm in female. Transverse width of the sacral hiatus at the base found 17.29±3.89 mm in male and 18.01±3.70 mm in female. Different in shape of sacral hiatus between male and female found statistically not significant. Location of apex of sacral hiatus was found highest in number at the level of 4th sacral vertebra (60.20%) and maximum location of base of the sacral hiatus was at the level of 5th sacral vertebra (91.20%). The sacral hiatus has anatomical variations and understanding of these variations may improve the success of caudal epidural anesthesia. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22690 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 31-36